Mucosal immunity and gut microbiota in dogs with chronic enteropathy. (February 2019) - Eissa, Nour; Kittana, Hatem; Gomes-Neto, João Carlos; Hussein, Hayam
Abstract: Chronic enteropathy (CE) in dogs is a chronic and relapsing immunopathology, of unknown etiology, that usually manifests with a plethora of clinical signs reflecting the underlying heterogeneity in its pathogenesis. Alterations of the mucosal immune responses and the gut microbiota composition are thought to play an essential role in CE. Similar to humans, it is hypothesized that the breakdown in mucosal tolerance leads to aberrant and pathological immune responses toward the gut microbiota, that in turn, may contribute to the severity of disease, at least for certain CE subsets. Therefore, in this review, we discuss some of the most relevant and recent insights microbiological and immunological aspects characterizing CE in dogs. Highlights: Dogs are affected by idiopathic chronic enteropathy (CE). Mucosal immune systems and gut microbiota are critical in maintaining the gut homeostasis. Aberrant immune responses and gut microbiota are major contributors to the pathogenesis of CE in dogs. Understanding the mechanisms associated with mucosal immunity and gut microbiota could offer novel therapeutics for CE.